ANALISIS PENGARUH MINAT, KARAKTER PRIBADI DAN MOTIVASI BERWIRAUSAHA TERHADAP ENTERPRENEURSHIP PADA MAHASISWA FAKULTAS SOSIAL SAINS DI UNIVERSITAS PEMBANGUNAN PANCA BUDI - Handriyani Dwilita (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
This study aims to analyze the effect of Interests, Personal Characteristics and Students of the Faculty of Social Affairs on Entrepreneurship. This research uses associative method with Multiple Linear Regression analysis technique. The variables observed were divided into two, namely the Entrepreneurship variable. , the independent variables are Interests, Personal Characters and Motivation. The results show that simultaneously the variables of Interest, Personal Character and Motivation affect the Entrepreneurship of Accounting Students. it is known that the independent variable has an effect of 42.2% on these variables.